Estudio del fenómeno turístico en Honda Tolima como destino multifacético (2022)
Colombia has been characterized for being a country with a great biodiversity, not only in flora and fauna, but also in cultural and historical aspects. This is the case of the municipality of Honda Tolima, which brings together all of the above, positioning itself as a territory with a great trajectory in historical and cultural tourism, and with a unique potential in nature tourism. From the research, nature tourism is seen as a very good option, since it has become increasingly popular among tourists, the motivations may vary, however, it is well known that due to the pandemic by covid 19, people prefer to have other types of experiences, rejecting mass tourism and preferring activities where they can have closer contact with nature and history. In the case of Honda, there is the possibility of implementing several activities and typologies, in addition to the interest of some service providers that have generated initiatives and undertakings of the community to enhance the tourism offer not only of the municipality, but also of the Tolima region.